2016
DOI: 10.1016/j.lindif.2016.08.017
|View full text |Cite
|
Sign up to set email alerts
|

Am I in the right place? Academic engagement and study success during the first years at university

Abstract: Entrance to university does not automatically lead to high academic engagement and success, and there may be individual differences in student engagement. In the present study, university students' (N=668) academic engagement and disengagement profiles, and the differences between them in terms of academic achievement, were investigated. Students from introductory courses were classified by Latent Profile Analysis (LPA) into homogenous groups having similar patterns according to the following variables: study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(46 citation statements)
references
References 78 publications
1
43
0
2
Order By: Relevance
“…This, however, depends on there being a sufficient understanding of the social support profiles of doctoral students and the various positive and negative indicators associated with the profiles. As most of the studies mentioned above mainly use a variable-oriented approach, they succeed in detecting and describing overall tendencies but may not disclose differently functioning subgroups of individuals and the complex relationships between variables associated with these subgroups (see Bergman & Andersson, 2010;Ketonen et al, 2016). Therefore, the person-centered approach ( Bergman & Andersson, 2010;Bergman & Magnusson, 1997) applied in this study could contribute to doctoral education literature by revealing group differences not detected in previous studies.…”
Section: Burnout Researcher Community and Supervisory Supportmentioning
confidence: 89%
“…This, however, depends on there being a sufficient understanding of the social support profiles of doctoral students and the various positive and negative indicators associated with the profiles. As most of the studies mentioned above mainly use a variable-oriented approach, they succeed in detecting and describing overall tendencies but may not disclose differently functioning subgroups of individuals and the complex relationships between variables associated with these subgroups (see Bergman & Andersson, 2010;Ketonen et al, 2016). Therefore, the person-centered approach ( Bergman & Andersson, 2010;Bergman & Magnusson, 1997) applied in this study could contribute to doctoral education literature by revealing group differences not detected in previous studies.…”
Section: Burnout Researcher Community and Supervisory Supportmentioning
confidence: 89%
“…The findings of Elina et al's study (2016) showed that students' participation and interaction with the education process was useful in terms of academic achievement and progress, and the results of this study showed that the higher the AE is, the higher their academic achievement will be, which is consistent with the current research. Ketonen et al (2016) has taken into account the individual differences of the learners, such as the amount of interest, attention, and learning, the physical conditions, such as fatigue, the uncertainty about the professional choice of the university discipline, etc. However, the present study has considered only the components of age, gender, and indigenous status [37].…”
Section: Discussionmentioning
confidence: 99%
“…Ketonen et al (2016) has taken into account the individual differences of the learners, such as the amount of interest, attention, and learning, the physical conditions, such as fatigue, the uncertainty about the professional choice of the university discipline, etc. However, the present study has considered only the components of age, gender, and indigenous status [37]. Schlenker et al (2013) also concluded that scientific interaction during teaching process, student academic performance, and academic grades, like a triangular model, could be influenced by each other during the education process, which is consistent with the results of this study, suggesting the impact of teaching quality on the AE [38].…”
Section: Discussionmentioning
confidence: 99%
“…These result are influenced by the condition in which first year at the university is undergoing a phase of transition from highschool students to university students. A wide range of dispositions, conceptions, motivational tendencies and prior knowledge color the way an individual students sees their new learning environment [8], so that the behavior demonstrated by everyone is the response of the overall condition.…”
Section: Freshmen' Pro-environmental Behavior In Daily Practicementioning
confidence: 99%
“…First year for the university (undergraduate) students is an important phase to adapt to life at the university, where the literature consistently mentions that first year was an important stage in shaping student attitudes and affects the persistence [8]. In this situation, proenvironmental behaviour adopting the process is very possible through the influence at the university current conditions.…”
Section: Introductionmentioning
confidence: 99%